Are cruise ship trips to Antarctica still acceptable? A careful consideration - Küpper, Thomas; Heggie, Travis (Health Promotion & Physical Activity, 2026)
Background: Cruise tourism to Antarctica has increased extensively in recent years. It can be assumed that this has had an impact on the environment. Methods: Searches were conducted in international specialist databases (e.g. Medline, Web of Science) and electronic media using various combinations of the keywords ‘Antarctica’, ‘tourism’, ‘cruise ships’, ‘environment’, ‘damage’ and ‘pollutants’ (January 1990 to January 2026). Only electronic media that met standard scientific requirements (authorship, source references, etc.) were included. The search results are summarised and evaluated. Results: There is a significant impact of tourism on the region. This includes, among other things, the disruption of breeding grounds, the release of various types of pollutants, the introduction of non-native species, soil compaction and other factors. The extent of the damage increases with the number of visitors. Conclusion: Due to its extreme ecological sensitivity, Antarctica is not suitable for large-scale tourism. The continent should be reserved for scientific research and otherwise strictly protected. Practically everything that tourists can see and experience there can also be seen in less sensitive locations. At the very least, tourism should be much more strictly regulated and monitored than it has been to date, and the number of visitors should be drastically reduced.